Identification of sulcatol, a potential pheromone of the ambrosia beetle Gnathotrichus materiarius (Col., Scolytidae) - Flechtmann, CAH; Berisford, C. W. (Blackwell Verlag Gmbh, 2003)
We report the identification of a potential pheromone for Gnathotrichus materiarius (Fitch) (Col., Scolytidae). The population sex ratio is close to 1:1, and males initiate attacks on host trees. Headspace and hindgut samples from single males showed the presence of the putative pheromone 6-methyl-5-hepten-2-ol, sulcatol. Unmated males released sulcatol for at least 12 days, and ceased producing the pheromone after 20 days. The peak sulcatol release occurred after 2 days. Males cease production of sulcatol 24 h after being paired with females. Single females were unable to initiate galleries, and no sulcatol was detected from their headspace and hindgut samples. The chiral ratio of the pheromone, observed from headspace samples, was 31% (S)-(+)- and 69% (R)-(-)-sulcatol.
Keywords: enantiomeric ratio; headspace analysis; hindgut analysis; SPME technique; sex ratio